My garden - Henkes, Kevin. (Greenwillow Books, 2010)
After helping her mother weed, water, and chase the rabbits from their garden, a young girl imagines her dream garden complete with jellybean bushes, chocolate rabbits, and tomatoes the size of beach balls.